Quelle(s) épidémiologie(s) pour la santé au travail ? Réflexions à partir des cancers professionnels - Charles-Olivier Betansedi (Perspectives Interdisciplinaires sur le Travail et la Santé)
Since the early 1990s, epidemiology has been marked by lively debates about the nature of the discipline and the role it should play in society. Based on a critical review of the literature on occupational cancers, this article explores the different conflicts arising from the main divergent epidemiological paradigms, and underlines their social foundations and logic. Drawing as it does on various disciplines, occupational epidemiology is therefore subject to competing and contradictory theoretical and explanatory rationales, which are evident in the choice of hypotheses, subjects of study, and variables of interest. More specifically, this article indicates how the conflicts and oppositions that take place between disciplines (medicine, social sciences, etc.) reoccur within the field of epidemiology itself and in each of its branches, and this as a result of the field’s growing hyper-specialization and the opposition between "nature" and "culture" that structures the entire field.